Longitudinal change in collagen degradation biomarkers in idiopathic pulmonary fibrosis: an analysis from the prospective, multicentre PROFILE study. Issue 6 (June 2015) - Jenkins, R Gisli; Simpson, Juliet K; Saini, Gauri; Bentley, Jane H; Russell, Anne-Marie; Braybrooke, Rebecca; Molyneaux, Philip L; McKeever, Tricia M; Wells, Athol U; Flynn, Aiden; Hubbard, Richard B; Leeming, Diana J; et al.
Summary Background Idiopathic pulmonary fibrosis, a progressive and inevitably fatal disorder, has a highly variable clinical course. Biomarkers that reflect disease activity are urgently needed to inform patient management and for use as biomarkers of therapeutic response (theragnostic biomarkers) in clinical trials. We aimed to determine whether dynamic change in markers of extracellular matrix (ECM) turnover predicts progression of idiopathic pulmonary fibrosis as determined by change in forced vital capacity and death. Methods In this ongoing prospective, multicentre, observational cohort study (PROFILE), participants with idiopathic pulmonary fibrosis or idiopathic non-specific interstitial pneumonia diagnosed within the preceding 6 months were recruited from two coordinating centres (Nottingham, UK, and, Royal Brompton Hospital, London, UK). Serum samples were prospectively collected at baseline, 1 month, 3 months, and 6 months and were analysed for a panel of novel matrix metalloprotease (MMP)-degraded ECM proteins, by ELISA-based, neoepitope assay. 11 neoepitopes were tested in a discovery cohort of 55 patients to identify biomarkers of sufficient rigour for more detailed analyses. Eight were then further assessed in a validation cohort of 134 patients with 50 age-matched and sex-matched controls. Changes in biomarker concentrations were related to subsequent progression of idiopathic pulmonary fibrosis (defined as death or decline in forced vital capacity >10% at 12 months after study enrolment) using a repeated measures model. The PROFILE study is registered on ClinicalTrials.gov, numbers NCT01134822 and NCT01110694. Findings Of 214 eligible participants recruited between Sept 1, 2010, and March 31, 2012, 189 had a confirmed diagnosis of idiopathic pulmonary fibrosis and were included in subsequent analyses. In the discovery cohort, mean concentrations of seven neoepitopes (BGM, p=0·009; C1M, p=0·009; C3M, p=0·046; C6M, p=0·032; CRPM, p=0·008; ELM2, p=0·02; and VICM, p=0·0007) differed significantly between healthy controls and participants with idiopathic pulmonary fibrosis. Baseline concentrations of six neoepitopes (C1M, p=0·012; C3A, p=0·012; C3M, p=0·0005; C6M, p=0·0003; CRPM, p=0·021; and VICM, p=0·046) were significantly higher in patients with progressive idiopathic pulmonary fibrosis (n=32) than in those with stable disease (n=23). In the validation cohort, mean concentrations of C1M (p=0·001), C3M (p=0·044), C6M (p=0·003), and CRPM (p=0·024) at baseline were higher in patients with idiopathic pulmonary fibrosis than in healthy controls. When assessed longitudinally, concentrations of six neoepitopes (BGM, C1M, C3A, C3M, C6M, and CRPM) were significantly higher in patients with progressive idiopathic pulmonary fibrosis (n=71) than in patients with stable idiopathic pulmonary fibrosis (n=60) by 6 months. Baseline concentrations of two neoepitopes were associated with increased mortality (C1M: HR 1·62 [95% CI 1·14–2·31], p=0·0069; C3A: 1·91 [1·06–3·46], p=0·032). The rate of change between baseline and 3 months of six neoepitopes (BGM: HR 1·084 [95% CI 1·03–1·14], p=0·0019; C1M: 1·01 [1·003–1·017], p=0·0039; C3M: 1·106 [1·045–1·170], p=0·0005; C5M: 1·003 [1·001–1·005], p=0·0011; C6M: 1·042 [1·007–1·078], p=0·017; and CRPM: 1·38 [1·16–1·63], p=0·0002) was strongly predictive of overall survival, and the increased risk was proportional to the magnitude of change in neoepitope concentrations. The strongest association with 3-month rate of biomarker change was recorded for CRPM; greater than 0 ng/mL per month conferred a HR of 2·16 (95% CI 1·15–4·07), whereas a rate greater than 1 ng/mL per month resulted in an HR 4·08 (2·14–7·8), and a rate greater than 1·7 ng/mL per month was associated with an HR 6·61 (2·74–15·94). Interpretation Concentrations of protein fragments generated by MMP activity are increased in the serum of individuals with idiopathic pulmonary fibrosis compared with healthy controls. Increased neoepitope concentrations were associated with disease progression, and the rate of this increase predicted survival. Serial measurements of neoepitopes have potential to be used as theragnostic biomarkers in clinical trials and to guide management of idiopathic pulmonary fibrosis. Funding GlaxoSmithKline R&D and the Medical Research Council.